Influence of scoring methods and numerical superiority on physical demands in elite young soccer players - Javier Sánchez-Sánchez; Javier Raya-González; Daniel Castillo; Rodrigo Ramírez-Campillo; Mario Sánchez; Alejandro Rodríguez-Fernández; Fabio Y Nakamura (Asociación Española de Ciencias del Deporte, 2021)
Small-sided games (SSGs) are a useful strategy to optimize the training process in soccer. The modification of some variables simultaneously implies several physical adaptations in soccer players. Thus, the aim of this study was to analyze the differences in the physical demands encountered by soccer players in different SSGs formats focusing on the scoring methods (i.e., mini-goals and regular goals with goalkeepers) and to the numerical superiority situations (i.e., no superiority, variable superiority, and fixed superiority). Eight elite young soccer players from the same team (age: 17.9 ± 1.1 years) randomly completed six SSG formats. Physical parameters (i.e., total distance [TD], distance covered at different speeds [D1, D2, D3, D4, D5 and D6], and distance covered accelerating [ACC] and decelerating [DEC]) were collected. The main results showed that the variable superiority (i.e., 4vs4+1) situation is more demanding, in terms of TD and distance covered at D3 and D4, in comparison to no superiority (i.e., 4vs4) and fixed superiority (i.e., 5vs4) situations both SSGs played with mini-goals and regular goals with goalkeepers. Besides, higher physical demands were registered in fixed superiority (i.e., 5vs4) than in no superiority (i.e., 4vs4) situation. Finally, only in a no superiority (i.e., 4vs4) situation higher distances at D1 and D5 were registered during the SSG played with mini-goals but higher distance at D3 was covered in the SSG format with regular goals and goalkeepers. Playing SSGs in variable superiority situation is more demanding in comparison to no superiority (i.e., 4vs4) and fixed superiority situations both during those SSGs played with mini-goals and/or regular goals and goalkeepers. In addition, SSGs played with mini-goals induced higher physical demands than playing with regular goals and goalkeepers during no superiority games. These findings could be useful for coaches in order to periodize the training drills within the microcycle to modulate the training session intensity.